2014
DOI: 10.1680/macr.13.00276
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage of naturally corroded bars in reinforced concrete structures

Abstract: The bond properties of naturally corroded reinforced concrete members were experimentally investigated. Thirteen specimens were taken from the northern edge beam of Stallbacka Bridge, a girder bridge in Sweden. The specimens exhibited different levels of corrosion-induced damage, including concrete cracking and cover spalling. The damage was carefully documented and the specimens were tested in suspended four-point bending tests. Their general behaviour was monitored through measurements of applied loads and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The confinement resulting from the reclosing of cracks by the applied load could be the reason, as already mentioned by Cairns et al (2008). The presence of stirrups and the non-uniform damage around the bars induced by natural corrosion could also be an explanation Hanjari et al (2011), Tahershamsi et al (2014. • Stirrup corrosion did not lead to stirrup failure since no premature splitting of the compressive strut was recorded during the tests.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The confinement resulting from the reclosing of cracks by the applied load could be the reason, as already mentioned by Cairns et al (2008). The presence of stirrups and the non-uniform damage around the bars induced by natural corrosion could also be an explanation Hanjari et al (2011), Tahershamsi et al (2014. • Stirrup corrosion did not lead to stirrup failure since no premature splitting of the compressive strut was recorded during the tests.…”
Section: Resultsmentioning
confidence: 88%
“…The same observation was not made by Hanjari, Coronelli, and Lundgren (2010), who conducted the pull-out tests on beam ends corroded by impressing a direct current on the surface of the steel bars. In contrast, experiments carried out on naturally corroded specimens have shown that bond strength is higher when the corrosion of rebars is non-uniform because of the presence of parts of the bar perimeter that are not affected by corrosion Tahershamsi, Hanjari, Lundgren, and Plos (2014). Moreover, the presence of stirrups, even severely corroded, leads to significant residual bond and anchorage capacity Hanjari, Coronelli, and Lundgren (2011).…”
Section: Anchorage Capacitymentioning
confidence: 97%
“…a significant bond still exists between corroded bars and concrete (Hanjari, Coronelli, & Lundgren, 2011;Tahershamsi, Hanjari, Lundgren, & Plos, 2014;, plastic deformation only occurred at mid-span during the threepoint bending test. As a result, it was expected that plastic strains affected only a limited area of reinforcing bars at midspan and the 450 mm length pieces retrieved from the tension reinforcement of both corroded and non-corroded beams were not suffer plastic deformation before the tension tests.…”
Section: Mechanical Properties Of the Reinforcementmentioning
confidence: 98%
“…Moreover, failure of control beam (A1T-B) was a consequence of the re-bar slipping on the support. This result may appear surprising, as it is usually accepted that corrosion reduces the bond stress [37], it must be borne in mind that the natural corrosion process [38] confinement due to both the corroded stirrups [39] and the reactive force on the support modify the bond capacity as shown by Cairns et al [40]. Moreover, natural corrosion of beam A1CL3-B did not lead to corrosion all around the perimeter of the re-bars and so did not result in the same change in bond strength as the accelerated corrosion induced by impressed current that is usually described in literature.…”
Section: Mid-span Lvdtmentioning
confidence: 99%